The Impact of State-Wide Exit Exams in Germany: A Descriptive Case Study - van Ackeren, Isabell; Block, Rainer; Klein, Esther Dominique; Kühn, Svenja Mareike (Education Policy Analysis Archives, 2012)
This study analyzes the possible intended and unintended impact of statewide exit exams as a governance tool used by education authorities. In a descriptive case study based on quantitative empirical research, three German states (Baden-Württemberg, Rhineland-Palatinate, North Rhine-Westphalia) with differing exit exam traditions (statewide versus school-based) are compared. Consistent with other recent research findings, the potential influences of statewide exit exams on teaching and learning processes can be detected for mathematics, but not for German or biology. In particular, these influences show in the fact that teachers whose students have to take a statewide exit exam are less responsive to students’ interests regarding the choice of topics in the classroom, perceive a tendency to narrow the delivered curriculum and increase cooperation with other teachers. In addition, both teachers and students feel a higher pressure to perform and perceive their roles to be different −they see themselves as allies preparing for an externally set exam. Teachers also tend to feel “de-professionalized”. In those areas where statewide exams do seem to affect schooling, most of the results are consistent with what was intended by the authorities when they introduced the exams, and there are only few unintended side-effects. From a governance perspective, however, a general capacity of statewide exit exams to move schooling in a desired direction remains rather doubtful, particularly considering the fact that the exam procedures that have recently been implemented in the German states are very heterogeneous and only partly standardized.